Analisis Rasio Neutrofil-Limfosit sebagai Penanda Inflamasi pada Ibu Hamil dengan Preeklampsia di RS Gotong Royong Surabaya - Yustisia Amalia; Miftahul Khairoh; Arkha Rosyaria Badrus (Rena Cipta Mandiri, 2026)
Background: Preeclampsia is a pregnancy complication associated with systemic inflammation and endothelial dysfunction. The neutrophil-to-lymphocyte ratio (NLR) is a simple hematological parameter that can be used as an inflammatory marker.Objective: This study aimed to analyze NLR as an inflammatory marker in pregnant women with preeclampsia at Gotong Royong Hospital Surabaya.Methods: This study used an observational analytic design with a cross-sectional approach. The sample consisted of 40 pregnant women with preeclampsia. Data were obtained from medical records and complete blood count results.Results: A total of 28 respondents (70%) had preeclampsia without severe features, while 12 respondents (30%) had preeclampsia with severe features. The median NLR among all respondents was 3.85. The median NLR in the preeclampsia with severe features group was higher than in the group without severe features, at 5.42 and 3.18, respectively. Statistical analysis showed a significant association between NLR and preeclampsia severity, with p=0.001.Conclusion: NLR has the potential to serve as a simple inflammatory marker in pregnant women with preeclampsia.